Ontogeny of the cranial bones of the giant amazon river turtle Podocnemis expansa Schweigger, 1812 (Testudines, Podocnemididae) - Lucélia Gonçalves Vieira (Acta Scientiarum. Biological Sciences, 2010)
In order to determine the normal stages of formation in the sequence of ossification of the cranium of Podocnemis expansa in its various stages of development, embryos were collected starting on the 18th day of natural incubation and were subjected to bone diaphanization and staining. In the neurocranium, the basisphenoid and basioccipital bones present ossification centers in stage 19, the supraoccipital and opisthotic in stage 20, the exoccipital in stage 21, and lastly the prooptic in stage 24. Dermatocranium: the squamosal, pterygoid and maxilla are the first elements to begin the ossification process, which occurs in stage 16. However, ossification centers begin to appear in stage 17 in most of these bone elements, i.e., the frontal, jugal, postorbital, parietal, premaxilla and prefrontal, followed by the palatine and quadratojugal in stage 19 and lastly by the vomer in stage 25. The quadrate bone of the splanchnocranium ossifies in stage 23. The mandible and hyoid apparatus, the dentary, coronoid and supra-angular, show ossification centers in stage 16 and the branchial horn I in stage 17. The sequence and synchronization of ossification in P. expansa show similarities as well as differences when compared with other species of Testudines.